Promoting Sustainable Fruit and Vegetable Biowaste Management and Industrial Symbiosis through an Innovative Web Platform - Ioannis Varvaringos; Eva Skourtanioti; Georgios Letsos; Evgenia Rizoudi; Ektoras Makras; Margarita Panagiotopoulou; Sofia Papadaki; Katerina Valta (Waste, 2023)
Sustainable bioeconomy is a promising pathway towards the transition to a circular and climate-neutral economy. The valorization of biowaste is a key player in this direction. This paper presents the design and development of the AgriPLaCE Platform, which aims to promote synergies that enable the utilization of biowaste from the fruit and vegetable supply chain. The platform consists of the AgriPLaCE Waste Management Database, which provides users with an extended list of potential utilization methods for various types of fruit and vegetable biowaste streams, and the AgriPLaCE Synergies Tool, which facilitates synergies between different actors involved in the biowaste-to-resource value chain from agricultural waste production to waste treatment and new valuable products’ exploitation. Initially, the conceptual design of both tools took place based on analysis of user needs and services alongside the system architecture. Following this, the AgriPLaCE Platform was developed with the implementation of all the necessary subsystems. The results of the platform’s implementation demonstrated its potential to generate multiple collaborations and synergies while users can also deepen their knowledge about alternative and emerging treatment technologies and valuable products from a wide range of fruit and vegetable biowaste streams.